Apaci - Nikolic, Miroslav (Serbia and Montenegro : Film I Ton - VideoPress, 2002)
A propaganda documentary about the Serbian community living in the Sirinic valley in Kosovo. The director attempts to depict the tense and dangerous life-situation in which the people of this area live. However, the film is full of nationalistic innuendoes and is mocking the SFOR.
Duration: 00:25:00
Keywords: Documentary films